EXPLORING THE IMPACT OF AI TOOLS ON EFL LEARNERS' COMMUNICATION AND AUTONOMY - Adrian Adrian; Pupung Purnawarman (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines the impact of AI tools on EFL learners’ communication skills and learner autonomy across varying proficiency levels. Employing an exploratory mixed-methods design that combined a 15-item Likert-scale survey with open-ended questions, data were collected from 16 purposively selected EFL learners enrolled in an undergraduate English program at an Indonesian university. The small sample was deemed appropriate for qualitative exploration rather than statistical generalization. Grammarly was used primarily for writing correction and grammatical feedback; ChatGPT supported conversational practice and essay drafting; and Duolingo provided gamified vocabulary and pronunciation exercises. Participants reported improvements in grammar accuracy, vocabulary range, and writing confidence, with gains most pronounced among beginner and intermediate learners. Advanced learners, however, expressed frustration with idiomatic expressions and cultural nuances, identifying a ceiling effect in the utility of AI tools at higher proficiency levels. Regarding autonomy, participants described using the tools for self-directed error review and goal setting, yet several acknowledged a tendency toward passive dependency, accepting AI corrections without critical reflection. These findings suggest that AI tools can complement traditional instruction but require human oversight, blended feedback strategies, and teacher scaffolding to ensure cultural and linguistic appropriateness. This study contributes to emerging research on AI in EFL by foregrounding learner autonomy and contextual challenges as proficiency-dependent variables that prior single-level studies have not fully addressed.